Pendampingan UMKM Rambak Mladri Melalui Pembuatan Logo dan Kemasan Serta Inovasi Penggunaan Media Online - Prafiota, Diva; Pradani, Duma Dian Agi; Larasati, Ines Adela; Ramadhan, Tegar Alfis; Dasmadi, Dasmadi (Society : Jurnal Pengabdian Masyarakat, 2023)
Based on the result of the Rambak Mladri MSME assistance activities owned by Satiyem, it is known that knowledge about product branding through making logos and packaging is still lacking, the use of digital technology through digital media such as Instagram, Facebook, and WhatsApp is also still low. In this session MSME actorsÂ  are assisted in making logos and packaging that mobile, digital marketing through social media and providing education about the benefits and dangers of reducing social media, as well as providing location points on Google Maps so that virtual customers in society are easier to find. Looking for the location of MSME Rambak Mladri Satiyem which is in Mladri RT 04 RW 02, Tempursari village, Sambi, Boyolali.